Moral Aqidah Learning: Perspectives from Grade 3 Stakeholders: Pembelajaran Aqidah Moral: Wawasan dari Siswa Kelas 3, Guru, dan Orang Tua - Uswatun Hasanah; Nur Maslikhatun Nisak (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study investigates the implementation of Akidah Akhlak (Moral Aqidah) learning in shaping the moral development of Grade 3 students at MI AL-KHAWATIM, Arjasa District, Sumenep Regency. The study utilizes data collected through observations, interviews, and document analysis, employing descriptive qualitative techniques for data analysis. The subjects involved in the research include students, teachers, and parents. The findings reveal that the implementation of moral aqidah learning effectively utilizes question and answer sessions, discussions, lectures, and relevant learning resources. The study highlights the advantages of this approach in shaping students' behavior and attitudes towards God, parents, teachers, and themselves. However, challenges such as classroom distractions and limited learning resources were identified. The validity of the data was tested using triangulation. The implications of this research offer insights into improving moral aqidah education and its impact on students' moral formation. Highlights: Effective implementation of moral aqidah: This study explores the successful implementation of moral aqidah learning, emphasizing the use of various teaching methods and resources. Challenges in moral aqidah education: The research highlights the drawbacks of implementing moral aqidah learning, including classroom distractions, limited resources, and potential confusion among students. Implications for moral formation: The findings of this study provide valuable insights into the significance of moral aqidah education in shaping students' behavior, attitudes, and relationships with God, parents, teachers, and themselves. Keywords: moral aqidah, implementation, qualitative research, moral formation, learning methods.